2022
DOI: 10.1021/acs.langmuir.2c01439
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Shrinkage of Microfluidically Generated Microbubbles by Tuning Lipid Concentration

Abstract: Monodisperse microbubbles with diameters less than 10 μm are desirable in several ultrasound imaging and therapeutic delivery applications. However, conventional approaches to synthesize microbubbles, which are usually agitation-based, produce polydisperse bubbles that are less desirable because of their heterogeneous response when exposed to an ultrasound field. Microfluidics technology has the unique advantage of generating size-controlled monodisperse microbubbles, and it is now well established that the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(41 citation statements)
references
References 61 publications
2
39
0
Order By: Relevance
“…In a recently published paper, we found a linear relationship between the initial diameter, D i , of bubbles and their post-shrinkage final diameter, D f . 17 We also found that when the continuous lipid phase concentration is decreased, bubbles experience increased levels of shrinkage. 17 We suggest that this happens because when bubbles form in a solution of higher lipid concentration, more lipid molecules are initially adsorbed onto the gas–liquid interface in comparison with bubbles produced using a lower lipid concentration solution.…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations
“…In a recently published paper, we found a linear relationship between the initial diameter, D i , of bubbles and their post-shrinkage final diameter, D f . 17 We also found that when the continuous lipid phase concentration is decreased, bubbles experience increased levels of shrinkage. 17 We suggest that this happens because when bubbles form in a solution of higher lipid concentration, more lipid molecules are initially adsorbed onto the gas–liquid interface in comparison with bubbles produced using a lower lipid concentration solution.…”
Section: Resultsmentioning
confidence: 58%
“…This means D f is approximately 6.7 times smaller than D i . Therefore, in this paper, we expand the previous research 17 by hypothesizing that decreasing the initial diameter D i of MBs and the concentration of the lipid solution would further increase the degree of shrinkage and lead to the formation of BNBs. We also hypothesize that the size of the resulting BNBs can be tuned by adjusting the initial diameter D i of MBs, and the lipid solution concentration.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…In other works, which are destined to form micro- and nano-bubbles, similar strategy of solvent extraction can be adopted. The bubble size can further be controlled by the maximum packing density of lipids at the gas–liquid interface [ 105 ].…”
Section: Methods Of Submicron Droplets Generationmentioning
confidence: 99%